Market Dynamics in Infrastructure: A Comprehensive Analysis of Financial Factors Shaping Stock Prices - Mubarok, Faizul; Lyadi, Citra Febria; Fizriyah, Nurul; Syaiful, Dzikra Nisa (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
This research explores the complex dynamics between financial performance and stock prices in the infrastructure sector. The main focus draws attention to key variables such as Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), Company Size (FZ), and Interest Rates (INRT). This research produces significant findings Through quantitative methods and a panel regression model. The analysis shows that ROA significantly influences share prices, highlighting the importance of efficient financial performance in attracting investor interest. Meanwhile, as a liquidity indicator, CR has a significant relationship with stock prices, indicating that financial health can impact investor perceptions. Financial sustainability, reflected in DER, yields the exciting finding that a lower proportion of debt is associated with valuations from the stock market. Company size (FZ) has also been shown to influence share prices, highlighting the importance of operational scale in increasing investor confidence. However, Interest Rates (INRT) do not significantly influence share prices in the infrastructure sector. The results of this research provide valuable insights for stakeholders, helping them understand the link between financial performance and stock market behavior in the context of the infrastructure sector. The implications of these findings can guide more informational and data-based managerial policies and investment decisions.